2014
DOI: 10.1002/gcc.22167
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in UGT genes modify the associations of NSAIDs with risk of colorectal cancer: Colon cancer family registry

Abstract: The use of non-steroidal anti-inflammatory drugs (NSAIDs) is associated with reduced risk of colorectal neoplasia. Previous studies have reported that polymorphisms in NSAID-metabolizing enzymes central to NSAID metabolism including UDP-glucuronosyltransferases (UGT) and cytochrome P450 (CYP) 2C9 may modify this protective effect. We investigated whether 35 functionally relevant polymorphisms within CYP2C9 and UGT genes were associated with colorectal cancer risk or modified the protective effect of NSAIDs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…Moreover, the rs13129471 A>G polymorphism of UGT2B4 was significantly associated with breast cancer after adjusting for ethnicity . Scherer et al observed an association between a UGT2B15 polymorphism and increased risk of colorectal cancer. Vidal et al reported African American men who carry the wild‐type functional UGT2B15 gene have an elevated risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rs13129471 A>G polymorphism of UGT2B4 was significantly associated with breast cancer after adjusting for ethnicity . Scherer et al observed an association between a UGT2B15 polymorphism and increased risk of colorectal cancer. Vidal et al reported African American men who carry the wild‐type functional UGT2B15 gene have an elevated risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study in a larger population validated this potential interaction between ibuprofen use and the PPARG Pro12Ala variant in modifying rectal cancer risk ( P for interaction =0.03) [107]. Other studies in colorectal cancer patients have reported significant interactions between ibuprofen use and genetic variants of CYP2C9 ( CYP2C9 * 2 and * 3 ) [105], SMAD7 (rs4939827 and rs4464148) [104], and UGT2B4 (rs1131878, rs1966151, and rs13119049) [106], but not PTGS2 (rs68946, rs20432, and rs5275) [99]. Studies in men with advanced prostate cancer have suggested that the protective effect of ibuprofen may be modified by the LTA C +80A ( P for interaction =0.008) [102] and PTGS2 rs2745557 ( P for interaction =0.12) [101] variants, but the numbers of ibuprofen users in these studies were relatively small.…”
Section: Pharmacogenomicsmentioning
confidence: 96%
“…One UGT1A1 SNP (rs887829) exhibited significant association with warfarin use with T -allele carriers requiring higher doses than for individuals with the CC genotype (6.3 compared with 5.2 mg/d, respectively). In a study of 1600 colorectal cancer patients and 2500 unaffected siblings, the variation in 4 UGT genes ( UGT1A3, UGT1A6, UGT2B4 , and UGT2B15 ) modified risk of colorectal cancer either independently of interactively with nonsteroidal anti-inflammatory use (79). Variants in the promoter of the UGT1A1 gene (UGT1A1*28, rs8175347), which result in 5, 7, or 8 repeats instead of 6 thymine-adenine repeats, were associated with decreased UGT1A1 transcription and higher serum bilirubin with increased numbers of thymine-adenine repeats (75, 82).…”
Section: Etiology Of the Heterogeneity In Flavonoid Admementioning
confidence: 99%